The Fibonacci Numbers The numbers are: 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . . Each Fibonacci number is the sum of the previous two Fibonacci numbers! Let n any positive integer. If Fn is what we use to describe the nth Fibonacci number, then Fn = Fn−1 + Fn−2 Trying to prove: F1 + F2 + · · · + Fn = Fn+2 − 1 We proved a theorem about the sum of the first few Fibonacci numbers: Theorem For any positive integer n, the Fibonacci numbers satisfy: F1 + F2 + F3 + · · · + Fn = Fn+2 − 1 The “even” Fibonacci Numbers What about the first few Fibonacci numbers with even index: F2 , F4 , F6 , . . . , F2n , . . . Let’s call them “even” Fibonaccis, since their index is even, although the numbers themselves aren’t always even!! The “even” Fibonacci Numbers Some notation: The first “even” Fibonacci number is F2 = 1. The second “even” Fibonacci number is F4 = 3. The third “even” Fibonacci number is F6 = 8. The tenth “even” Fibonacci number is F20 =??. The nth “even” Fibonacci number is F2n . HOMEWORK Tonight, try to come up with a formula for the sum of the first few “even” Fibonacci numbers. 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . . Let’s look at the first few: F2 + F4 = 1 + 3 = 4 F2 + F4 + F6 = 1 + 3 + 8 = 12 F2 + F4 + F6 + F8 = 1 + 3 + 8 + 21 = 33 F2 + F4 + F6 + F8 + F10 = 1 + 3 + 8 + 21 + 55 = 88 See a pattern? 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . . It looks like the sum of the first few “even” Fibonacci numbers is one less than another Fibonacci number. But which one? F2 + F4 = 1 + 3 = 4 = F5 − 1 F2 + F4 + F6 = 1 + 3 + 8 = 12 = F7 − 1 F2 + F4 + F6 + F8 = 1 + 3 + 8 + 21 = 33 = F9 − 1 F2 + F4 + F6 + F8 + F10 = 1 + 3 + 8 + 21 + 55 = 88 = F11 − 1 Can we come up with a formula for the sum of the first few “even” Fibonacci numbers? 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . . Let’s look at the last one we figured out: F2 + F4 + F6 + F8 + F10 = 1 + 3 + 8 + 21 + 55 = 88 = F11 − 1 The sum of the first 5 even Fibonacci numbers (up to F10 ) is the 11th Fibonacci number less one. Maybe it’s true that the sum of the first n “even” Fibonacci’s is one less than the next Fibonacci number. That is, Conjecture For any positive integer n, the Fibonacci numbers satisfy: F2 + F4 + F6 + · · · + F2n = F2n+1 − 1 Trying to prove: F2 + F4 + · · · F2n = F2n+1 − 1 Let’s try to prove this!! We’re trying to find out what F2 + F4 + · · · F2n is equal to. Well, let’s proceed like the last theorem. Trying to prove: F2 + F4 + · · · F2n = F2n+1 − 1 We know F3 = F2 + F1 . So, rewriting this a little: F2 = F3 − F1 Also: we know F5 = F4 + F3 . So: F4 = F5 − F3 In general: Feven = Fnext odd − Fprevious odd Let’s put these together: Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1 F2 = F3 − F1 F4 = F5 − F3 F6 = F7 − F5 F8 = F9 − F7 .. .. . . F2n−2 = F2n−1 − F2n−3 F2n = F2n+1 − F2n−1 Adding up all the terms on the left sides will give us something equal to the sum of the terms on the right sides. Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1 F2 = /F//3 − F1 F4 = F5 − /F//3 F6 = F7 − F5 F8 = F9 − F7 .. .. . . F2n−2 = F2n−1 − F2n−3 + F2n = F2n+1 − F2n−1 Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1 F2 = /F//3 − F1 F4 = /F//5 − /F//3 F6 = F7 − /F//5 F8 = F9 − F7 .. .. . . F2n−2 = F2n−1 − F2n−3 + F2n = F2n+1 − F2n−1 Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1 F2 = /F//3 − F1 F4 = /F//5 − /F//3 F6 = /F//7 − /F//5 F8 = F9 − /F//7 .. . .. . F2n−2 = F2n−1 − F2n−3 + F2n = F2n+1 − F2n−1 Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1 F2 = /F//3 − F1 F4 = /F//5 − /F//3 F6 = /F//7 − /F//5 F8 = /F//9 − /F//7 .. . .. . F2n−2 = F2n−1 − /F//2n−3 ///// + F2n = F2n+1 − F2n−1 Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1 F2 = /F//3 − F1 F4 = /F//5 − /F//3 F6 = /F//7 − /F//5 F8 = /F//9 − /F//7 .. . .. . F2n−2 = /F//2n−1 ///// − /F//2n−3 ///// + F2n = F2n+1 − /F//2n−1 ///// Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1 F2 = /F//3 − F1 F4 = /F//5 − /F//3 F6 = /F//7 − /F//5 F8 = /F//9 − /F//7 .. . .. . F2n−3 F2n−2 = /F//2n−1 ///// − //////// + F2n = F2n+1 − //////// F2n−1 F2 + F4 + F6 + · · · + F2n = F2n+1 − F1 Trying to prove: F2 + F4 + · · · + F2n = F2n+1 − 1 F2 = /F//3 − F1 F4 = /F//5 − /F//3 F6 = /F//7 − /F//5 F8 = /F//9 − /F//7 .. . .. . F2n−3 F2n−2 = /F//2n−1 ///// − //////// + F2n = F2n+1 − //////// F2n−1 F2 + F4 + F6 + · · · + F2n = F2n+1 − 1 Trying to prove: F2 + F4 + · · · F2n = F2n+1 − 1 This proves our second theorem!! Theorem For any positive integer n, the even Fibonacci numbers satisfy: F2 + F4 + F6 + · · · + F2n = F2n+1 − 1 The “odd” Fibonacci Numbers What about the first few Fibonacci numbers with odd index: F1 , F3 , F5 , . . . , F2n−1 , . . . Let’s call them “odd” Fibonaccis, since their index is odd, although the numbers themselves aren’t always odd!! The “odd” Fibonacci Numbers Some notation: The first “odd” Fibonacci number is F1 = 1. The second “odd” Fibonacci number is F3 = 2. The third “odd” Fibonacci number is F5 = 5. The tenth “odd” Fibonacci number is F19 =??. The nth “odd” Fibonacci number is F2n−1 . 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . . Let’s look at the first few: F1 + F3 = 1 + 2 = 3 F1 + F3 + F5 = 1 + 2 + 5 = 8 F1 + F3 + F5 + F7 = 1 + 2 + 5 + 13 = 21 F1 + F3 + F5 + F7 + F9 = 1 + 2 + 5 + 13 + 34 = 55 See a pattern? 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . . It looks like the sum of the first few “odd” Fibonacci numbers is another Fibonacci number. But which one? F1 + F3 = 1 + 2 = 3 = F4 F1 + F3 + F5 = 1 + 2 + 5 = 8 = F6 F1 + F3 + F5 + F7 = 1 + 2 + 5 + 13 = 21 = F8 F1 + F3 + F5 + F7 + F9 = 1 + 2 + 5 + 13 + 34 = 55 = F10 Can we come up with a formula for the sum of the first few “even” Fibonacci numbers? 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, . . . Maybe it’s true that the sum of the first n “odd” Fibonacci’s is the next Fibonacci number. That is, Conjecture For any positive integer n, the Fibonacci numbers satisfy: F1 + F3 + F5 + · · · + F2n−1 = F2n F1 + F3 + · · · + F2n−1 = F2n Trying to prove: Let’s try to prove this!! We know F2 = F1 . So, rewriting this a little: F1 = F2 Also: we know F4 = F3 + F2 . So: F3 = F4 − F2 In general: Fodd = Fnext even − Fprevious even Trying to prove: F1 + F3 + · · · + F2n−1 = F2n F1 = F2 F3 = F4 − F2 F5 = F6 − F4 F7 = F8 − F6 .. .. . . F2n−3 = F2n−2 − F2n−4 + F2n−1 = F2n − F2n−2 Adding up all the terms on the left sides will give us something equal to the sum of the terms on the right sides. Trying to prove: F1 + F3 + · · · + F2n−1 = F2n F1 = /F//2 F3 = F4 − /F//2 F5 = F6 − F4 F7 = F8 − F6 .. .. . . F2n−3 = F2n−2 − F2n−4 + F2n−1 = F2n − F2n−2 Trying to prove: F1 + F3 + · · · + F2n−1 = F2n F1 = /F//2 F3 = /F//4 − /F//2 F5 = F6 − /F//4 F7 = F8 − F6 .. .. . . F2n−3 = F2n−2 − F2n−4 + F2n−1 = F2n − F2n−2 Trying to prove: F1 + F3 + · · · + F2n−1 = F2n F1 = /F//2 F3 = /F//4 − /F//2 F5 = /F//6 − /F//4 F7 = F8 − /F//6 .. . .. . F2n−3 = F2n−2 − F2n−4 + F2n−1 = F2n − F2n−2 Trying to prove: F1 + F3 + · · · + F2n−1 = F2n F1 = /F//2 F3 = /F//4 − /F//2 F5 = /F//6 − /F//4 F7 = /F//8 − /F//6 .. . .. . F2n−3 = F2n−2 − /F//2n−4 ///// + F2n−1 = F2n − F2n−2 Trying to prove: F1 + F3 + · · · + F2n−1 = F2n F1 = /F//2 F3 = /F//4 − /F//2 F5 = /F//6 − /F//4 F7 = /F//8 − /F//6 .. . .. . F2n−4 F2n−3 = /F//2n−2 // ///// − ////// + F2n−1 = F2n − /F//2n−2 ///// F1 + F3 + · · · + F2n−1 = F2n Trying to prove: F1 + F3 + · · · + F2n−1 = F2n This proves our third theorem!! Theorem For any positive integer n, the Fibonacci numbers satisfy: F1 + F3 + F5 + · · · + F2n−1 = F2n So far: Theorem (Sum of first few Fibonacci numbers.) For any positive integer n, the Fibonacci numbers satisfy: F1 + F2 + F3 + · · · + Fn = Fn+2 − 1 Theorem (Sum of first few EVEN Fibonacci numbers.) For any positive integer n, the Fibonacci numbers satisfy: F2 + F4 + F6 + · · · + F2n = F2n+1 − 1 Theorem (Sum of first few ODD Fibonacci numbers.) For any positive integer n, the Fibonacci numbers satisfy: F1 + F3 + F5 + · · · + F2n−1 = F2n One more theorem about sums: Theorem (Sum of first few SQUARES of Fibonacci numbers.) For any positive integer n, the Fibonacci numbers satisfy: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 We’ll take advantage of the following fact: For each Fibonacci number Fn Fn+1 = Fn + Fn−1 Fn = Fn+1 − Fn−1 Fn2 = Fn · Fn = Fn · (Fn+1 − Fn−1 ) Fn2 = Fn · Fn+1 − Fn · Fn−1 Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 Let’s check this formula for a few different valus of n: Fn2 = Fn · Fn+1 − Fn · Fn−1 n = 4: F42 = F4 · F4+1 − F4 · F4−1 F42 = F4 · F5 − F4 · F3 32 = 3 · 5 − 3 · 2 9 = 15 − 6 It works for n = 4! Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 Let’s check this formula for a few different valus of n: Fn2 = Fn · Fn+1 − Fn · Fn−1 n = 8: F82 = F8 · F8+1 − F8 · F8−1 F82 = F8 · F9 − F8 · F7 212 = 21 · 34 − 21 · 13 441 = 714 − 273 = 441 It works for n = 8! Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 Let’s use this formula: Fn2 = Fn · Fn+1 − Fn · Fn−1 To find out what the sum of the first few SQUARES of Fibonacci numbers is: F12 + F22 + F32 + · · · + Fn2 =???? Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 We’re using: Fn2 = Fn · Fn+1 − Fn · Fn−1 F12 = F1 · F2 F22 = F2 · F3 − F2 · F1 F32 = F3 · F4 − F3 · F2 F42 = F4 · F5 − F4 · F3 .. . .. . 2 Fn−1 = Fn−1 · Fn − Fn−1 · Fn−2 + Fn2 = Fn · Fn+1 − Fn · Fn−1 Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 F12 = /F//1//·//F/2/ F22 = F2 · F3 − //////// F2 · F1/ F32 = F3 · F4 − F3 · F2 F42 = F4 · F5 − F4 · F3 .. . .. . 2 Fn−1 = Fn−1 · Fn − Fn−1 · Fn−2 + Fn2 = Fn · Fn+1 − Fn · Fn−1 Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 F12 = /F//1//·//F/2/ F22 = /F//2//·//F/3/ − //////// F2 · F1/ F32 = F3 · F4 − //////// F3 · F2/ F42 = F4 · F5 − F4 · F3 .. . .. . 2 Fn−1 = Fn−1 · Fn − Fn−1 · Fn−2 + Fn2 = Fn · Fn+1 − Fn · Fn−1 Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 F12 = /F//1//·//F/2/ F22 = /F//2//·//F/3/ − //////// F2 · F1/ F32 = /F//3//·//F/4/ − //////// F3 · F2/ F4 · F3/ F42 = F4 · F5 − //////// .. . .. . 2 Fn−1 = Fn−1 · Fn − Fn−1 · Fn−2 + Fn2 = Fn · Fn+1 − Fn · Fn−1 Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 F12 = /F//1//·//F/2/ F22 = /F//2//·//F/3/ − //////// F2 · F1/ F32 = /F//3//·//F/4/ − //////// F3 · F2/ F42 = /F//4//·//F/5/ − //////// F4 · F3/ .. . .. . 2 Fn−1 = Fn−1 · Fn − F · Fn−2 n−1 //// /////////// + Fn2 = Fn · Fn+1 − Fn · Fn−1 Trying to prove: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 F12 = /F//1//·//F/2/ F22 = /F//2//·//F/3/ − /F//////// 2 · F1 F32 = /F//3//·//F/4/ − /F//////// 3 · F2 F42 = /F//4//·//F/5/ − /F//////// 4 · F3 .. . .. . 2 Fn−1 =F n−1 · Fn−2 //n−1 //////·//F/n+1 //// − F ////////////// / + Fn2 = Fn · Fn+1 − //////////// Fn · Fn−1 F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 Our fourth theorem: Theorem (Sum of first few SQUARES of Fibonacci numbers.) For any positive integer n, the Fibonacci numbers satisfy: F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 So far: Theorem (Sum of first few Fibonacci numbers.) F1 + F2 + F3 + · · · + Fn = Fn+2 − 1 Theorem (Sum of first few EVEN Fibonacci numbers.) F2 + F4 + F6 + · · · + F2n = F2n+1 − 1 Theorem (Sum of first few ODD Fibonacci numbers.) F1 + F3 + F5 + · · · + F2n−1 = F2n Theorem (Sum of first few SQUARES of Fibonacci numbers.) F12 + F22 + F32 + · · · + Fn2 = Fn · Fn+1 Examples 1 + 2 + 5 + 13 + 34 + 89 + 233 + 610 + 1597 + 4181 = 6765 1+1+4+9+25+64+169+441+1156+3025+7921 = 89·144 = 12816 Now, complete this worksheet .....